2022
DOI: 10.1108/gkmc-01-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

E-leadership and virtual communication adoption by educators: an UTAUT3 model perspective

Abstract: Purpose The purpose of the study is to explore the various determinants of virtual communication technology (VCT) adoption among higher educational leaders by applying Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) model. Further, this study ascertains the relationship among the various determinants and measure the effects of these determinants in adoption of VCT by educational leaders. Design/methodology/approach The study was conducted by using online survey method for data collection from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…The recent Covid 19 pandemic forced various educational institutions and academic leaders to shift educational related activity from physical mode to the virtual or hybrid mode (Ashour et al ., 2021). With the change in the educational work structure with a rise of dependency on electronic communication, the educational leaders have to manage and coordinate with the VCT (Vella, 2021; Gupta et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent Covid 19 pandemic forced various educational institutions and academic leaders to shift educational related activity from physical mode to the virtual or hybrid mode (Ashour et al ., 2021). With the change in the educational work structure with a rise of dependency on electronic communication, the educational leaders have to manage and coordinate with the VCT (Vella, 2021; Gupta et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2017). Although, both TAM and UTAUT models are highly applicable and cited in technology acceptance and use in higher education context (Sánchez-Prieto et al ., 2019; Teo and Zhou, 2017; Gupta et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, out of 11 non-randomised quantitative studies only three [86,89,120] met all the criteria assigned to this category. While one of these studies [6] failed to meet any criteria, the remaining eight studies showed limited level of representativeness in the sample [61,78], incomplete reporting of data [30] and the insufficient account of confounders in design and analysis [100].…”
Section: Rq3: To What Extent Did Such Research Meet the Established Q...mentioning
confidence: 99%
“…Functional Ed Tech research may sometimes omit to acknowledge more challenging issues of technology innovation that relate to wider issues beyond local instructional design contexts, such as trust, ethics, surveillance, and the potential harms of technology, as well as issues of social context, power structures, privilege, and social justice [104][105][106]129]. Functional Ed Tech tends to focus on classroom teaching and learning with technology, learning Ann & Aziz [10]; Ashbaugh [18]; Burnette [32]; Bogler et al [30]; Garst et al [54]; Ghafur [55]; Gupta et al [61]; Guthrie et al [63]; Hornor [67]; Kotula et The two aspects of Digital and Leadership are explicitly brought together with recognition of inherent tension between them to form a more balanced new concept with some preference still evident, some acknowledgement of risks and leaders' role in managing the tension is present, this may manifest as brief references to trust and power dynamics with regards to stakeholders and technology.…”
Section: Tablementioning
confidence: 99%